Cultivating an Informed Empathy: An Aspiring Teacher Examines his Talk and Actions - Mary Louise Gomez; Amy Johnson Lachuk (Foxton Books, 2018)
This text traces the development of an aspiring biracial teacher's growing understandings of African American youth he tutors. It deploys a Bakhtinian conceptual framework for how we might develop new understandings of ourselves through relationships and dialogues with others. It offers examples from one aspiring teacher's experiences to illustrate how when individuals look inward, that they can come to different interpretations of who people are and why they behave as they do. Further, it